Persistent Pulmonary Hypertension of the Newborn: Analysis of 181 cases over one Year (Cardiovascular Journal, 2018)
Background: Persistent pulmonary hypertension (PPHN) is the persistence of the high pulmonary arterial pressure after birth which is a characteristic of the fetal circulation. PPHN is associated with substantial infant mortality and morbidity. Various treatment protocol are used according to the need of the patient. This study aimed to see the spectrum of the disease and its outcome in Bangladesh.Methods: 181 newborn babies were diagnosed as persistent pulmonary hypertension or persistent fetal circulation. After establishing diagnosis, all cases were kept in NICU and various management plans were prescribed according to necessity of a specific case. Repeat echocardiography was done after 72 hours to see the response of treatment. Residual congenital cardiac lesions were managed later on.Results: Most of the patient (69.06%) was diagnosed at first week of life. Minimum age of the patient was 1 day and maximum age 23 days. Among 181 cases 109 (66.22%) were male and 72(39.77%) were female. Associated congenital lesions like atrial septal defect was found in 52 (28.72%) cases, patent ductus arteriosus (PDA) was found in 14 (7.73%) cases and ventricular septal defect (VSD) was found in 2 (1.10%) cases. Combination of ASD & PDA was found in 75 (44.33%) cases. Systolic pulmonary artery pressure was more than 60 mmHg in 103 (56.91%) cases, more than 50 mmHg in 53 (29.28%) cases and more than 30 mmHg in 25 (13.81%) cases. Most of the patient (100%) received high flow oxygen therapy along with anti failure (66.30%) and sildenafil 98 (54.14%) therapy as per requirement of the patient. Complete cure was achieved in 95.58% cases and mortality was only 1.10%.Conclusion: These data showed a very impressive outcome of the PPHN in Bangladeshi Newborn even with minimally invasive management.Cardiovasc. j. 2018; 11(1): 17-22